Superoxide Dismutase (SOD) Level In Lung Of Doca-Salt Hypertension Rat Treated By Methanolic Extract Of Tea And Mango Parasite - Aini, Siti Qurrotul; Sjakoer, Nour Athiroh Abdoes; Mubarakati, Nurul Jadid (Metamorfosa: Journal of Biological Sciences, 2021)
Hypertension is a condition caused by the pressure of blood against the artery walls when the blood is Hypertension is a condition caused by the pressure of blood against the artery walls when the blood is pumped from the heart to the tissues. In hypertension, it can stimulate the formation of reactive oxygen species (ROS) compounds. The use of exogenous antioxidants in preventing oxidative stress can alternatively use herbal plants. For example, herbal plants such as tea parasites and mango parasites can increase the activity of superoxide dismutase (SOD) and reduce the concentration of malondialdehyde (MDA). This study aims to further examine the role of methanolic extracts from the combination of tea parasite and mango parasite (EMBTBM) on superoxide dismutase (SOD) in hypertensive rats exposed to DOCA-salt using experimental methods. Using 25 male Wistar rats, consisted of 5 treatments, namely control (-), control (+), the treatment group for the combination of tea parasites and mango parasites with doses of 50, 100, and 200 mg / KgBB respectively with five repetitions. The results of this study indicate that the level of increased SOD with the combination of EMBTBM in the control group (+) was very significantly different from the control group (-), treatment 1, 2, and 3. This very significant difference was due to the p-value = <0.001 (< 0.05). The benefit of this study is that it can be used as a reference for the role of the combination of tea parasites and mango parasites on superoxide dismutase (SOD) in hypertensive rats exposed to DOCA-salt. Keywords : Hypertension, EMBTBM, SOD .